Detecting dysplasia using white light endoscopy or chromoendoscopy in ulcerative colitis patients without primary sclerosing cholangitis: A systematic review and meta-analysis. (April 2018) - Azizi, Saeed; Al-Rubaye, Hussein; Turki, Mohammed Adil A.; Siddiqui, Muhammad R. Sameem; Shanmuganandan, Arun P.; Ehsanullah, Bushra; Brar, Ranjeet; Abulafi, Al-Mutaz
Abstract: Background: Endoscopic examinations are a vital diagnostic tool for dysplasia. Establishing the precision of different modes of examination is essential due to the disparate pick-up rates of dysplasia. Objective: The aim of this article was to establish the pick-up rates of dysplastic or cancerous lesions using white light endoscopy (WLE) and random/targeted biopsies, or chromoendoscopy (CE), in patients with ulcerative colitis (UC) without primary sclerosing (PSC) or Crohn's disease (CD). Data sources: A systematic review to identify all studies up to November 2017, without language restriction, was conducted from PubMed, the Cochrane Controlled Trials Register (1960–2017), MEDLINE, CINAHL and EMBASE (1981–2017). MeSH and text word terms used included "ulcerative colitis", "dysplasia", "random biopsy", "targeted biopsy", "colonoscopy", "white light", and "chromoendoscopy". Further searches were performed using the bibliographies of these articles. Study selection: All studies reporting on colonoscopy detection rates of dysplasia and cancers in UC without involvement of PSC or CD were included. There was no age restriction to include patients. Data extraction: Outcome data were extracted by 2 authors independently using outcome measures defined a priori. Quality assessment was performed using the Newcastle-Ottawa scales. Data synthesis: Data were extracted and analysed according to meta-analytical techniques using comprehensive meta-analysis. The pooled overall pick-up rate of dysplastic/cancerous lesions on WLE random biopsies was 5.6% [Event rate 0.06 (0.01, 0.23), df = 4, I2 = 94%]. Using a combined random and targeted approach with WLE the incidence was 5.1% [Event rate 0.05 (0.03, 0.09), df = 4, I2 = 96%]. One study reported on CE and found a 7% pick-up rate for dysplastic lesions. Conclusions: Endoscopic examination of UC patients without PSC identifies dysplastic or cancerous lesions in 5–7% of cases. WLE and random biopsies may pick-up a similar number of lesions to targeted biopsies, however the number of biopsies may need to be greater to achieve this equivalence. CE has a slightly higher pick-up rate. Further comparative studies are required to strengthen the body of evidence. Highlights: Endoscopic examination of UC patients without PSC identifies dysplastic or cancerous lesions in 5–7% of cases. WLE with a large number of random biopsies may pick-up a similar number of lesions to a targeted biopsy approach. CE has a slightly higher pick-up rate. Further comparative studies are required to strengthen the body of evidence.